Neonatal BCG has no effect on allergic sensitization and suspected food allergy until 13 months. Issue 6 (5th September 2017) - Thøstesen, Lisbeth Marianne; Kjaer, Henrik Fomsgaard; Pihl, Gitte Thybo; Nissen, Thomas Nørrelykke; Birk, Nina Marie; Kjærgaard, Jesper; Jensen, Aksel Karl Georg; Aaby, Peter; Olesen, Annette Wind; Stensballe, Lone Graff; Jeppesen, Dorthe Lisbeth; Benn, Christine Stabell; et al.
Abstract: Background: Vaccination with Bacillus Calmette‐Guérin (BCG) is used in many countries as protection against tuberculosis. Studies have suggested that BCG may also have non‐specific effects, reducing non‐tuberculosis mortality, morbidity, and atopic manifestations. In this study, we evaluated the effect of neonatal BCG vaccination on allergic sensitization and suspected food allergy at 13 months of age. Methods: The Danish Calmette Study was conducted from 2012 to 2015 at three Danish hospitals. Within 7 days of birth, the 4262 newborns of 4184 included mothers were randomized 1:1 to BCG or to a no‐intervention control group. Exclusion criteria were gestational age <32 weeks, birth weight <1000 g, known immunodeficiency, or no Danish‐speaking parent. Follow‐up information was collected through telephone interviews at 3 and 13 months of age. Subgroups of participants were offered blood sampling at 13 months of age. Results: By 13 months of age, the parents and/or general practitioners of 5.6% (117/2089) of the children in the BCG group and 6.1% (126/2061) of the control group suspected food allergy, resulting in a risk ratio comparing BCG‐vaccinated children with control children of 0.91 (95% CI 0.71‐1.16). Among 1370 blood samples, sensitization (Phadiatop Infant >0.35 kUA/L) was found in 55 of 743 (7.4%) children in the BCG group and 50 of 627 (8.0%) of the control group (risk ratio 0.94 [0.65‐1.36]). Conclusion: In this randomized clinical trial, neonatal BCG had no significant effect on suspected food allergy or on sensitization at 13 months of age. Abstract :